PENGEMBANGAN MEDIA KARTU UNO DALAM PEMBELAJARAN EKONOMI - Putri Nabilah; Warneri Warneri; Husni Syahrudin (Universitas Tanjungpura, 2020)
Abstract This research motivated by a learning system that is still conventional with lectures and assignments or group work and the use of learning media is still minimal at the beginning of the semester so that students are less enthusiastic in learning. The purpose of this study to produce learning media, namely the Uno Card media so that students are enthusiastic and active in the learning process. The research procedure used the PPE (development model Planning, Production, and Evaluation)by Richey and Klein. Data collection techniques is qualitative in the form of revisions by media experts and interviews and quantitative data from assessment questionnaires. The results of this study: (1) The assessment of Learning Practitioners is 0.99 from 0-1 by using CVR & CVI calculations which are declared valid or suitable for use. (2) Student assessment obtained 0.92 from 0-1 range by using CVR & CVI calculations declared valid or suitable for use. Keywords: Development, Kartu Uno, Ecenomic Learning